Role of nuclear rotation in dissociation of H+2 in a short laser pulse - Anis, Fatima; Esry, B. D. (My University, 2008)
We revisit the problem of H+2 in an intense, short laser pulse to investigate the role of nuclear rotation and thus gauge the validity of the more common aligned molecule approximation. For the laser parameters considered, our results show rough qualitative agreement, but not quantitative agreement. In one case, however, the aligned molecule approximation deviates even qualitatively from the more complete calculation by overestimating the importance of vibrational trapping.